Implementasi Media Pembelajaran Berbasis Visual Interaktif untuk Meningkatkan Pemahaman Rambu Lalu Lintas pada Siswa Sekolah Dasar - Taufan, Rahmat; Sarwandi; Khairani Djahara; Inkha Ameriza; Yulia Fitri Ananda; Zahra Suci Maulilovia (Prodi Pendidikan Guru Sekolah Dasar, 2026)
Traffic safety education constitutes a fundamental component of early character and civic development in elementary school students. However, students’ understanding of traffic signs remains relatively low, primarily due to the predominance of conventional and less engaging instructional approaches. This study aims to enhance the understanding of traffic signs among students of SDN 137 Pekanbaru through the implementation of interactive visual-based learning media. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 30 fifth-grade students of SDN 137 Pekanbaru in the 2024/2025 academic year. Research instruments included pre-tests and post-tests to measure students’ comprehension levels. The findings indicate a significant improvement in students’ understanding following the implementation of interactive visual-based learning media. In Cycle I, the average comprehension score reached 72.3 with 70% classical mastery, while in Cycle II, the average score increased to 85.7 with 90% classical mastery. Students’ responses also reflected positive enthusiasm toward the use of interactive visual media. In conclusion, the implementation of interactive visual-based learning media represents an effective alternative instructional strategy for improving elementary school students’ understanding of traffic signs.